PRODUKTIVITAS KARYAWAN: PENGARUH KECAKAPAN KERJA, SUPERVISI TRANSFORMASIONAL DAN KENYAMANAN BEKERJA STUDI KASUS PT S&F GARMEN MANUFAKTUR - Oktaviani, Dini; Suryani, Ni Nyoman; Mitariani, Ni Wayan Eka (Referensi : Jurnal Ilmu Manajemen dan Akuntansi, 2024)
This research has a purpose to analyze the influence of proficiency, transformational supervision and enjoyment of work on PT performance. SF Garment Manufacturing. This research is kind ofof quantitative analysis and consists ofo 32 employees as the research population and sample. Data collection is carried out through questionnaire techniques using survey method. Data analysis uses SPSS 23 software which includes multiple linear regression test, classical test and hypothesis test, Based on the results of the analysis, research shows that proficiency has significantly give a positive influence both simultaneously and partially on the employee productivity. Transformational supervision also has significantly give  a positive effect simultaneously and partially on employee productivity. Meanwhile, enjoyment of work simultaneously has significantly give a positive effect on PT performance. SF Garment Manufacturing. Research variables have coefficient determination 83,6% to influence the productivity of company’s employee. So, research in the future still needed to analyze other variable out from the research variables that already exist in this study.